To rewrite the equation \( \log_9(-x - 9) = -2 \) in exponential form, we need to use the definition of logarithms, which states that if \( \log_b(a) = c \), then \( b^c = a \).
Here, the base \( b \) is \( 9 \), the argument \( a \) is \( -x - 9 \), and \( c \) is \( -2 \).
Using the definition of logarithms, we can rewrite the equation as:
\[ 9^{-2} = -x - 9 \]
So the correct exponential form of \( \log_9(-x - 9) = -2 \) is:
\[ 9^{-2} = -x - 9 \]
Therefore, the correct response is:
9 superscript negative 2 baseline equals negative x minus 9.